Peningkatan Sikap Ibu terhadap Kesehatan Ibu dan Bayi Baru Lahir melalui Program Pendampingan Ibu Hamil di Tujuh Kabupaten/Kota di Indonesia - Anissa Rizkianti; Novianti Novianti; Suparmi Suparmi (Sekretariat Badan Penelitian dan Pengembangan Kesehatan, 2022)
This study aimed to measure the increase in maternal attitudes towards maternal and child health as a result of maternity mentoring program. Using quasi-experimental design, this study evaluated changes in attitudes of 280 pregnant women in the intervention and control groups in seven districts/cities in Indonesia. Intervention was one-on-one mentoring program to pregnant women by midwifery students and cadres. Results of the regression analysis showed that the scores of mothers' attitudes in each group were significantly different. The average score of maternal attitudes after mentoring increased by 5.7% in the intervention group (p = 0.000), and increased by 3.8% in the control group (p = 0.000). However, when comparing between the intervention and the control group, the difference in the mothers’ attitudes before and after mentoring was not significantly different (p = 0.655). Thus, maternal mentoring by students can be an alternative tool of education for pregnant women, and hopefully can be conducted sustainably by involving cross-sectoral coordination.